Investigation of the photon shielding capability of kaolin clay added with micro and nanoparticles of Bi2O3. (November 2022) - Almatari, M.; Koraim, Yousry; Saleh, I.H.; Sayyed, M.I.; Uddin Khandaker, Mayeen; Elsafi, M.
Abstract: In this work, the influence of adding nano and micro Bismuth-Oxide on the radiation shielding performance of kaolin clay was experimentally reported. The linear attenuation coefficient (LAC) of the prepared kaolin clays was measured using a HPGe detector between 0.06 and 1.333 MeV. To confirm the validity of the experimental results, the kaolin clay with micro-Bi2 O3 were matched with the XCOM results. The LAC findings demonstrated that the kaolin clay with nano-Bi2 O3 is better in attenuating the low energy photons than the micro-Bi2 O3 . The half value layer (HVL) decreases with adding micro Bi2 O3 to the kaolin clay. The pure KC shows a highest HVL and thus a high dimensional sample of the kaolin clay is needed to attenuate the radiation. At 0.081 MeV, the thickness of KC to attenuate 50% of the photons is 1.751 cm, while it is reduced to 0.332 cm for KC-Bi30. The radiation protection efficiency (RPE) for the kaolin clay -Bi10n is higher than kaolin clay -Bi10m and this is also valid for the 30% of Bi2 O3 . Hence, the kaolin clay with nano Bi2 O3 provides better radiation shielding compared to kaolin clay with micro Bi2 O3 and this is correct for the kaolin clay with 10 and 30% of Bi2 O3 . Highlights: LAC of the kaolin clay with different micro and nano Bi2 O3 was determined. KC with nano-Bi2 O3 is better in shield the low energy photons than the micro-Bi2 O3 . At 0.081 MeV, the thickness of KC to attenuate 50% of the photons is 1.751 cm. The RPE for the kaolin clay -Bi10n is higher than kaolin clay -Bi10m .